Mobile health technology and empowerment - Kreitmair, Karola V. (Bioethics, 2024)
Mobile Health (m-health) technologies, such as wearables, apps, and smartwatches, are increasingly viewed as tools for improving health and well-being. In particular, such technologies are conceptualized as means for laypersons to master their own health, by becoming “engaged” and “empowered” “managers” of their bodies and minds. One notion that is especially prevalent in the discussions around m-health technology is that of empowerment. In this paper, I analyze the notion of empowerment at play in the m-health arena, identifying five elements that are required for empowerment. These are (1) knowledge, (2) control, (3) responsibility, (4) the availability of good choices, and (5) healthy desires. I argue that at least sometimes, these features are not present in the use of these technologies. I then argue that instead of empowerment, it is plausible that m-health technology merely facilitates a feeling of empowerment. I suggest this may be problematic, as it risks placing the burden of health and behavior change solely on the shoulders of individuals who may not be in a position to affect such change.